Podobnosti in razlike v sistemu kolektivnega pogajanja v javnem in zasebnem sektorju - Kresal Šoltes, Katarina (Podjetje in delo, 2022)
Insufficiently clear regulatory framework may harm efficient collective bargaining. Efficient collective bargaining and greater collective bargaining coverage are among the key measures to insure decent work and reduce in-work poverty. In all EU Member States, the collective bargaining coverage rate would be at a level of at least 70%. This requirement is set out in the proposal for a directive on adequate minimum wages in the EU. Furthermore, in the proposal for a directive, the European Commission defines an adequate regulatory framework as one of the possible policy measures to promote the effectiveness of collective bargaining. The article compares the regulatory framework of the collective bargaining system in the public and private sector, and presents proposals de lege ferenda. The author focuses mainly on issues such as the autonomy of collective bargaining, parties and validity of the concluded collective agreement. The author states that the Slovenian legislation is based upon the fundamental principle of free and voluntary collective bargaining. The Collective Bargaining Act does not require the compulsory conclusion of collective agreements nor does it enumerate their compulsory content or types. However, the Public Sector Salary System Act lays down a number of specifics and differences, including mandatory content of the collective agreement for the public sector (the classification of jobs and titles in salary classes, amounts of salary supplements, etc.) and broad limitations of the principle in favorem. Moreover, this specific legal framework for the public sector is not sufficiently clear and precise.
Keywords: collective agreement; collective bargaining; decent work; dostojno delo; javni sektor; kolektivna pogajanja; kolektivne pogodbe; plače; public sector; sindikati; social partners; socialni partnerji; trade unions; wages